Intellectuals and “democratic elements”: A distrusted underclass - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
As the targets of numerous campaigns, intellectuals have sustained mental torment and physical suffering on a large scale. Like the deprivation of human rights for biological and genetic reasons in other lands or other ages, Chinese intellectuals were destined to suffer abridgement of their human rights in the People’s Republic of China for political and ideological reasons. The term “intellectuals” refers to all those who have had a middle school/higher education and those with similar educational levels. Included in the ranks of intellectuals were members of the so-called democratic parties. These people, never large in number, were mostly well educated and well known in intellectual circles. The Cultural Revolution will be long remembered by intellectuals not only as a period of continued mental torment from the earlier days, but more particularly as a period of the most cruel physical abuses in human history. Intellectuals, deprived of their most precious human rights, continue to exist in mainland China as an underclass. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China
Keywords: dept.his